2016
DOI: 10.1371/journal.pone.0162496
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Circulating microRNAs between Grazing and Grain-Fed Wagyu Cattle Are Associated with Altered Expression of Intramuscular microRNA, the Potential Target PTEN, and Lipogenic Genes

Abstract: We aimed to understand the roles of miRNAs in the muscle tissue maturation and those of circulating microRNAs (c-miRNAs) in beef production of Japanese Black (JB) cattle (Wagyu), a breed with genetically background of superior intermuscular fat depot, by comparing different feeding conditions (indoor grain-feeding vs. grazing on pasture). The cattle at 18 months old were assigned to pasture feeding or conventional indoor grain feeding conditions for 5 months. Microarray analysis of c-miRNAs from the plasma ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…bta-652_R+1 was downregulated (P = 0.0055) by maternal E+ treatment in MID gestation (E+/ E− and E+/E+) when compared with E−/E− treatment. Muroya et al (2016) also identified differential expression of bta-miR-652 levels in the LM of grass-fed cattle vs. grain-fed cattle. A partial gene target for miR-652 is phosphatase and tension homolog, which is responsible for inhibiting phosphatidylinositol-3-kinase (PI3K) signaling.…”
mentioning
confidence: 84%
“…bta-652_R+1 was downregulated (P = 0.0055) by maternal E+ treatment in MID gestation (E+/ E− and E+/E+) when compared with E−/E− treatment. Muroya et al (2016) also identified differential expression of bta-miR-652 levels in the LM of grass-fed cattle vs. grain-fed cattle. A partial gene target for miR-652 is phosphatase and tension homolog, which is responsible for inhibiting phosphatidylinositol-3-kinase (PI3K) signaling.…”
mentioning
confidence: 84%
“…Although initially thought to only act within the cell of production, it is now known that miRNAs are found in plasma and have been called circulating miRNAs (c-miRNAs) (Mooren et al 2014;Hubal et al 2016). c-miRNAs can be produced in one cell type and be transported in a paracrine-or endocrine-like fashion to effect distal tissues and influence tissue function (Valadi et al 2007;Hubal et al 2016;Muroya et al 2016). The plasma concentration of c-miRNAs goes up rapidly during exercise as does their intracellular expression (Safdar et al 2009;Russell et al 2013;Mooren et al 2014;Nielsen et al 2014b).…”
Section: Myokines/exerkines As Endocrine Mediators Of the Systemic Efmentioning
confidence: 99%
“…1 ) was associated with the lowest expression of bta-miR-2478 (Additional file 5 : Table S4) in macrophages challenged with ST12, compared to the other groups. However, it has also been reported that this miRNA is associated with energy metabolism and feeding-induced changes in muscles, and regulates different target genes in cattle [ 67 , 68 ]. This suggests that bta-miR-2478 may target other gene(s) than TGFβ1 in infected macrophages.…”
Section: Discussionmentioning
confidence: 99%